Morphological and molecular characterization of Nothopassalora personata from Argentina - Monguillot, Joaquín Humberto; Bernanrdi Lima, Nelson; Paredes, Juan Andrés; Giordano, Damián Francisco; Oddino, Claudio; Rago, Alejandro Mario; Carmona, Marcelo; Conforto, Erica Cinthia (Springer, 2023)
Late leaf spot (LLS) is the most important foliar disease of peanuts in Argentina and in other peanut production areas, causing defoliation and yield losses. In this study, six isolates obtained from symptomatic leaflets collected in Córdoba, Argentina, were characterized based on the morphology of the colony and conidia, as well as molecularly using a combination of the 28S nrRNA gene (LSU), the internal transcribed spacer regions and the intervening 5.8S nrRNA gene (ITS) of the rDNA operon, and the second largest subunit of RNA polymerase II (RPB2). Pathogenicity was confirmed using the detached leaf method, inoculating a spore suspension. Mycelial growth was evaluated on four culture media: peanut oatmeal agar (POA), potato dextrose agar (PDA), peanut leaflet extract agar (PLA) and peanut seed extract agar (PSA), with PSA and PDA showing the greatest radial growth. This is the first study of N. personata obtained in the peanut-producing region of Argentina.